Design and Experimental Study on Multifunction Liquid Cooling Camion for Military Aircrafts - Sheng Jian; Zhang Hua; Wu Zhaolin; Dou Binlin; Zhou Zhigang (Zhileng xuebao)
To satisfy the ground support requirements of the airborne liquid cooling system for aircraft repair or airport-related training, a new kind of multifunction ground liquid cooling camion for military aircrafts was designed and developed. This camion comprises five main parts, namely power supply system, coolant circulation system, cooling and heating system (single-stage vapor compression refrigeration cycle and electrical heater), electric control system, vehicle chassis, and body. Results showed that the functions of coolant supplementation to the liquid cooling camion, coolant internal circulation in the liquid cooling camion, coolant addition and drain for liquid cooling system on board, and hot/cold coolant external circulation from the liquid cooling camion to the liquid cooling system on board, are achieved in the sample liquid cooling camion. Moreover, the liquid cooling system satisfied the setting temperatures of 15 ℃ and 10 ℃ in the heating and cooling modes after 24 and 20 min, respectively. Accordingly, the environmental temperatures of heating and cooling were 5 ℃ and 30 ℃, whereas the coolant flow was 200 L/min for both modes, with a temperature fluctuation of ±0.5 ℃.